ANALYSIS OF THE DIFFICULTY OF DETERMINING THE MAIN IDEAS OF EACH PARAGRAPH IN ONE DISCUSSION OF THE 5TH GRADE STUDENTS OF BINTANG SERGAI PRIVATE ELEMENTARY SCHOOL - Gemala Widiyarti; Triayumi Triayumi (Sensei International Journal of Education and Linguistic, 2022)
This study aims to determine the difficulty of students in determining the main idea and to find out the factors that cause students to find it difficult to determine the main idea. The problem in this research is that there are students who still have difficulty in determining the main idea. This research was conducted in class V of Bintang Sergai Private Elementary School. By using the research subject of all fifth grade students at Bintang Sergai Private Elementary School. This type of research used is qualitative. Data collection techniques are tests and interviews. Data analysis technique uses descriptive. Based on the research results, the average score of all students in determining the main idea in narrative discourse was 49.08 out of 21 students. From the percentage of student scores obtained from the test results according to the location of the main sentence. Deductive paragraphs get a percentage rate of 71.42% in the very poor category, inductive paragraphs get a percentage rate of 76.19% in the very poor category and mixed paragraphs get a percentage of 80.95% in the very poor category. It can be concluded that students have difficulty determining the main sentence in mixed paragraphs. The causative factor is the lack of students' interest in learning the material to determine the main idea of a paragraph, the lack of use of media when the teacher teaches the material to determine the main idea of a paragraph which results in a lack of students' understanding of determining the main idea of a paragraph.